Therapeutic applications of artemisinin in ophthalmic diseases - Hao Sun; Ping Zhao; Lianghui Zhao; Zhizhong Zhao; Haoyu Chen; Cong Ren; Bin Guo (Heliyon)
Artemisinin is a sesquiterpene lactone extracted from the chrysanthemum plant, Artemisia annua. It is known for its curative effects in the treatment of pulmonary hypertension, leukemia, diabetes, malaria, and other diseases, owing to its abundant biological activity. In recent years, with the development of plant secondary metabolite research, other potential pharmacological effects of artemisinin-based drugs have received increasing attention; in particular, reports of their application for the potential treatment of ophthalmology-related diseases have gradually increased. Recently, studies confirmed that artemisinin plays therapeutic roles in eye diseases through regulation of signaling pathways, such asNrf2/HO-1/Keap1, TLR/MyD88/NF-κb, PI3K/AKT/mTOR, and FASN/Kmal-mTOR/SREBP1, and biological factors, such as protein kinase B, AMP-activated protein kinase, tumor necrosis factor alpha, nod-like receptor protein 3, vascular endothelial growth factor, malonyl-coenzyme A and cytochrome C. However, since ocular diseases are often caused by various factors, how artemisinin can play a good disease prevention role by modulating these factors needs to be further verified, and most of the current studies focus on in vitro and animal experiments, lacking sufficient information on clinical trial studies. To better explore and perfect the mechanism of action of artemisinin in ophthalmic diseases, and to better promote the clinical application of artemisinin, this study reviews the latest progress of artemisinin treatment for uveitis, uveal melanoma, age-related macular degeneration, diabetic retinopathy, ocular neovascularization, and dry eye, and it will provide theoretical support for the large-scale application of artemisinin in ophthalmic diseases in the future.